Application of GSN Safety Demonstration Method in Change Management of Product Safety Case - XU Zhengjie; WANG Qi (Kongzhi Yu Xinxi Jishu)
In the life cycle of product safety, safety cases are inevitably affected by changing regulatory requirements, additional safety evidence and design changes. In order to maintain an accurate description of system security, it is necessary to assess the impact of changes on the original security arguments. In this paper, the goal structuring notation (GSN) was used to construct the security demonstration change management model, and a clear security case change management analysis process was proposed to clearly express the interdependence between security objectives and security cases, so that the change can be reasoned and processed structurally and systematically. This method has been applied in the change management of rail transit signal equipment, and good results have been achieved.